Innovation Performance Review of Ukraine - Commission économique pour l'Europe des Nations unies (United Nations, 2016)
The Innovation Performance Review of Ukraine contains the outcomes of a policy advisory exercise that drew on the experience accumulated by the UNECE in the identification of good practices and policy lessons in the area of knowledge-based development, with particular reference to the problems of countries with economies in transition. It provides a set of recommendations and policy options to stimulate innovation activity in the country, enhance its innovation capacity and improve the overall efficiency of the national innovation system.